The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5650/jos.ess19214
|View full text |Cite
|
Sign up to set email alerts
|

The Colloidal and Oxidative Stability of the Sesame Pastes during Storage

Abstract: Introduction Sesame Sesamum indicum L. is one of the most important oilseed crops in the world, which contains up to 50 crude lipids, as well as high content of protein, minerals and vitamin 1. A diversity of the unique antioxidant compounds has been found from sesame seeds, including lipid-soluble sesamin, sesamol, sesamolin, and sesaminol, and water-soluble sesame lignan and lignan glucosides 2. Consumption of sesame seeds could lead to the increase of plasma tocopherol levels, which is helpful to prevent he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 15 publications
5
18
2
Order By: Relevance
“…All the samples exhibited increase in oil separation with storage time. This result is in agreement with the reports from other studies [10,46,47]. The result revealed that oil separation increased rapidly within the storage period of eight weeks and occurred somewhat slightly afterwards.…”
Section: Effect Of Storage Time On Oil Separationsupporting
confidence: 93%
See 4 more Smart Citations
“…All the samples exhibited increase in oil separation with storage time. This result is in agreement with the reports from other studies [10,46,47]. The result revealed that oil separation increased rapidly within the storage period of eight weeks and occurred somewhat slightly afterwards.…”
Section: Effect Of Storage Time On Oil Separationsupporting
confidence: 93%
“…The result revealed that oil separation increased rapidly within the storage period of eight weeks and occurred somewhat slightly afterwards. Similar observation was reported by Hou et al [46]. At the end of the 12 weeks storage period, the 100% sesame seed butter recorded the highest percentage of oil separation (3.19%) while the 30% sesame seed paste substituted butter recorded the least value (1.05%).…”
Section: Effect Of Storage Time On Oil Separationsupporting
confidence: 89%
See 3 more Smart Citations